(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this manuscript, we investigate fixed points for a subfamily of a non-expansive evolution(NeE) family of bounded linear operators on a Hilbert space H. Additionally, we utilize the concept of net and progression algorithm to establish several theorems regarding the strong convergence to a shared fixed point of the aforementioned subfamily. Finally, we furnish an example to bolster our findings.